Analysis of Service Tariffs and Customer Participation in the Purchase Decision of Prepaid Electricity Services at PT. PLN (Persero) Ulp Medan Kota Mediated by Corporate Image - Verianni Sinaga; Mesra b; Elfitra Desy Surya (Yayasan Multidimensi Kreatif, 2024)
This study aims to test and analyze the influence of service tariffs and customer participation on the purchase decision of prepaid electricity services at PT PLN (Persero) ULP Medan Kota and test and analyze the influence of service tariffs and customer participation on the purchase decision of prepaid electricity services at PT PLN (Persero) ULP Medan Kota mediated by the company's image. The type of research is quantitative, with an associative approach. The types of data used are primary and secondary. Data collection techniques with questionnaires and interviews. The sample of this study was taken by the Purposive Sampling method with the desired respondent criteria being customers who had visited the PLN (Persero) ULP Medan Kota office more than 2 times. The results of the study show that service tariffs and customer participation have a positive and significant effect on the decision to purchase prepaid electricity services at PT PLN (Persero) ULP Medan Kota, service tariffs and customer participation have a positive and significant effect on the decision to purchase prepaid electricity services at PT PLN (Persero) ULP Medan Kota which is mediated by the company's image.